2016
DOI: 10.1093/annonc/mdw163
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes with pemetrexed-based systemic therapies in RET-rearranged lung cancers

Abstract: Durable benefits with pemetrexed-based therapies in RET-rearranged lung cancers are comparable with ALK- and ROS1-rearranged lung cancers. When selecting therapies for patients with RET-rearranged lung cancers, pemetrexed-containing regimens should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 20 publications
1
67
1
Order By: Relevance
“…Fortunately, TKIs with more potent anti-RET activity are in advanced stages of clinical development [ 46 , 47 ]. Faced with that concern, clinicians frequently prescribed pemetrexed-containing chemotherapy, in agreement with the valuable results that have been reported in fusion gene-driven NSCLC [ 48 ]. In addition, although studies have suggested little or no benefit of immune checkpoint inhibitors in oncogene-driven tumors [ 49 ], some patients were given nivolumab.…”
Section: Discussionmentioning
confidence: 79%
“…Fortunately, TKIs with more potent anti-RET activity are in advanced stages of clinical development [ 46 , 47 ]. Faced with that concern, clinicians frequently prescribed pemetrexed-containing chemotherapy, in agreement with the valuable results that have been reported in fusion gene-driven NSCLC [ 48 ]. In addition, although studies have suggested little or no benefit of immune checkpoint inhibitors in oncogene-driven tumors [ 49 ], some patients were given nivolumab.…”
Section: Discussionmentioning
confidence: 79%
“…Reports have indicated that mutations in RET induce papillary carcinoma and familial medullary thyroid carcinoma in lung (27) and thyroid cancer (28). RET has been evidenced as an oncogene in a number of cancers, including head and neck squamous cell carcinoma (29), thyroid (30) and lung cancer (31). From the aspect mentioned above, targeting hNUDC with miR-449 may offer a novel strategy to prevent the oncogenic effect of RET in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In retrospective NSCLC series, RET rearrangement was significantly associated with increased levels of thymidylate synthase mRNA 67 and surprisingly high overall response rates (ORRs) (i.e., 40%) and progression-free survival (PFS) (i.e., 19 months) with pemetrexed-based chemotherapy. 74 However, a potential favorable prognosis associated with RET rearrangement or a generally higher chemosensitivity could be erroneously confounded with higher pemetrexed susceptibility. In terms of the prognostic value of RET rearrangement, in most retrospective series, RET did not significantly correlate with overall survival (OS) 10 or recurrence-free survival in resected lung cancer.…”
Section: Ret Inhibition In Nsclc: From Bench To Bedsidementioning
confidence: 99%